(untitled) (Research, Society and Development, 2022)
We aimed to investigate the impact of the suspension of orthodontic care during the Covid-19 pandemic on patients’ anxiety, treatment, and quality of life. This is a cross-sectional study conducted from data collected by an online questionnaire on Google Forms. A total of 65 questionnaires were evaluated, 37 from patients over 18 years old (adult group) and 28 from those responsible for patients under 18 years old (children/adolescents group). The questionnaire contained 27 questions, which addressed anxiety about the pandemic and treatment after discontinued care, and the impact of oral problems on quality of life (OHIP-14). According to the anxiety scale, adults were more anxious than children/adolescents about the pandemic (p=0.033). Adults showed a greater need for urgent care (p=0.002) or maintenance of treatment (p=0.040) than children/adolescents, and in both, private care was more sought after than public care (p=0.038). Speech problems (p=0.043) and severe pain (p=0.050) were more frequent in children/adolescents than in adults. Children/adolescents more often reported that life in general was made worse because of problems with their teeth, mouth, or braces, compared to adults (p=0.047). We concluded that adults and children/adolescents were anxious about the impacts of missed appointments during the Covid-19 pandemic on orthodontic treatment. The quality of life of the patients was affected by the suspension of care and was more relevant among children/adolescents.